Crystal structure of 2-chloro-1,3-bis(2,6-diisopropylphenyl)-1,3,2-diazaphospholidine 2-oxide - Alex J. Veinot; Arthur D. Hendsbee; Jason D. Masuda (Acta Crystallographica Section E: Crystallographic Communications, 2017)
The title compound, C26H38ClN2OP, was synthesized by reacting phosphoryl chloride with N,N′-bis(2,6-diisopropylphenyl)ethane-1,2-diamine in the presence of N-methylmorpholine which acted as an auxilliary base to quench the HCl released as a by-product. The resultant N-heterocyclic phosphine five-membered ring adopts a half-chair conformation and features a tetracoordinate P atom ligated by the chelating diamine [P—N = 1.6348 (14) and 1.6192 (14) Å], one double-bonded O atom [P1—O1 = 1.4652 (12) Å] and one Cl atom [P1—Cl1 = 2.0592 (7) Å]. The sterically hindered 2,6-diisopropylphenyl (Dipp) groups twist away from the central heterocycle, with torsion angles of −75.66 (19) and 83.39 (19)° for the P—N—Car—Car links. A number of intramolecular C—H...N, C—H...O and C—H...Cl close contacts occur. In the crystal, molecules are linked by C—H...O hydrogen bonds to generate [010] chains. C—H...π interactions are also observed.